Cost effectiveness of the addition of a comprehensive CT scan to the abdomen and pelvis for the detection of cancer after unprovoked venous thromboembolism. Issue 151 (March 2017) - Coyle, Kathryn; Carrier, Marc; Lazo-Langner, Alejandro; Shivakumar, Sudeep; Zarychanski, Ryan; Tagalakis, Vicky; Solymoss, Susan; Routhier, Nathalie; Douketis, James; Coyle, Douglas
Abstract: Importance: Unprovoked venous thromboembolism (VTE) can be the first manifestation of cancer. It is unclear if extensive screening for occult cancer including a comprehensive computed tomography (CT) scan of the abdomen/pelvis is cost-effective in this patient population. Objective: To assess the health care related costs, number of missed cancer cases and health related utility values of a limited screening strategy with and without the addition of a comprehensive CT scan of the abdomen/pelvis and to identify to what extent testing should be done in these circumstances to allow early detection of occult cancers. Participants and setting: Cost effectiveness analysis using data that was collected alongside the SOME randomized controlled trial which compared an extensive occult cancer screening including a CT of the abdomen/pelvis to a more limited screening strategy in patients with a first unprovoked VTE, was used for the current analyses. Main outcomes and measures: Analyses were conducted with a one-year time horizon from a Canadian health care perspective. Primary analysis was based on complete cases, with sensitivity analysis using appropriate multiple imputation methods to account for missing data. Results: Data from a total of 854 patients with a first unprovoked VTE were included in these analyses. The addition of a comprehensive CT scan was associated with higher costs (551 CDN) with no improvement in utility values or number of missed cancers. Results were consistent when adopting multiple imputation methods. Conclusions and relevance: The addition of a comprehensive CT scan of the abdomen/pelvis for the screening of occult cancer in patients with unprovoked VTE is not cost effective, as it is both more costly and not more effective in detecting occult cancer. Highlights: Cost effectiveness of comprehensive CT scan for cancer detection after unprovoked VTE is assessed. Comprehensive CT screening was more costly than limited screening alone. CT screening was not more effective in improving quality of life or detecting occult cancers. Implementing comprehensive CT screening after unprovoked VTE was not found to be cost effective.